Providing a Placental Transfusion in Newborns Who Need Resuscitation - Katheria, Anup C.; Brown, Melissa K.; Rich, Wade; Arnell, Kathy (Frontiers in Pediatrics, 2017)
Over the past decade there have been several studies and reviews on the importance of providing a placental transfusion to the newborn. Allowing a placental transfusion to occur by delaying the clamping of the umbilical cord is an extremely effective method of enhancing arterial oxygen content, increasing cardiac output and improving oxygen delivery. However, premature and term newborns that require resuscitation have impaired transitional hemodynamics and may warrant different methods to actively provide a placental transfusion while still allowing for resuscitation. In this review we will provide evidence for providing a placental transfusion in these circumstances and methods for implementation. Several factors including cord clamping time, uterine contractions, umbilical blood flow, respirations and gravity play an important role in determining placental transfusion volumes. Lastly, while many practitioners agree that a placental transfusion is beneficial it is not always straightforward to implement, and can be performed using different methods, making this basic procedure important to discuss. We will review three placental transfusion techniques: delayed cord clamping, intact umbilical cord milking and cut-umbilical cord milking. We will also review resuscitation with an intact cord and the evidence in term and preterm newborns supporting this practice. We will discuss perceived risks versus benefits of these procedures. Finally, we will provide key straightforward concepts and implementation strategies to ensure that placental-to-newborn transfusion can become routine practice at any institution.